Training on Ornamental Plant Cultivation using the Kokedama Technique in Tebang Kacang Village, Kubu Raya Regency - Zulfita, Dwi; Budi, Setia; Surachman, Surachman (International Journal of Public Devotion, 2025)
The majority of the people in Tebang Kacang village are Madurese who were displaced since the riots between the Madurese and Dayak ethnic groups in West Kalimantan in 2001. Until now, the Madurese people live in the village with very limited land available so that it is not possible to carry out agricultural cultivation which requires large land scale. The problem faced by the Dasa Wisma Mawar group of mothers who are partners in this PKM activity is that they are interested in carrying out an ornamental plant cultivation business, in the very limited time between their daily activities. This community service activity aims to increase knowledge and skills on how to make kokedama from moss and coco fiber for ornamental plants, increase knowledge about how to market kokedama products today. Implementation of service activities to empower housewives is carried out using lecture, discussion and demonstration methods. As a result of this service activity, overall participants liked the method of cultivating ornamental plants using the kokedama technique with a division of 14% preferring cultivation using the kokedama technique, 27% preferring cultivation using plastic flower pots and 53% preferred a combination of both.Pelatihan Budidaya Tanaman Hias dengan Teknik  Kokedama Di Desa Tebang Kacang Kabupaten Kubu RayaABSTRAKMasyarakat desa Tebang Kacang mayoritas adalah suku Madura yang mengungsi sejak   kerusuhan antar etnis Madura dan Dayak di Kalimantan Barat tahun 2001. Sampai sekarang masyarakat suku Madura tersebut tinggal menetap di desa tersebut dengan luas lahan yang disediakan sangat sempit sehingga tidak memungkinkan untuk melakukan budidaya pertanian yang memerlukan skala lahan yang besar. Titik permasalahan yang dihadapi oleh kelompok ibu-ibu Dasa Wisma Mawar yang menjadi mitra ada kegiatan PKM ini adalah berminat  untuk melakukan usaha budidaya tanaman hias, diantara waktu yang sangat terbatas pada kegiatan sehari-hari. Kegiatan  pengabdian kepada masyarakat ini bertujuan meningkatkan pengetahuan dan ketrampilan cara membuat kokedama dari lumut dan fiber coco utnuk media tanaman hias, meningkatkan pengetahuan tentang cara memasarkan produk kokedama di masa saat ini. Pelaksanaan kegiatan pengabdian pemberdayaan ibu rumah tangga dilakukan dengan metode ceramah, diskusi dan demonstrasi. Hasil dari kegiatan pengabdian  ini secara keseluruhan peserta menyukai cara budidaya tanaman hias dengan Teknik kokedama  dengan pembagian 14 % lebih menyukai budidaya dengan Teknik kokedama, 27% lebih menyukai budidaya menggunakan pot bunga plastik dan 53 % menyukai kombinasi keduanyaKata Kunci :Pelatihan; Tanaman Hias;  Teknik Kokedama